A Fluorogenic Triphenyl‐Amine‐Naphthyl‐Hydrazide Probe Selective for Cu2+ and Cysteine Detection via an ON‐OFF‐ON Logic path with Real Applications. Issue 48 (28th December 2020) - Paul, Sukanya; Dey, Sunanda; Pal, Kunal; Maity, Suvendu; Jana, Kuladip; Sinha, Chittaranjan
Abstract: 1, 1′‐((1E, 1′E)‐((2E, 2′E)(((phenylazanediyl)bis(4, 1‐phenylene))bis‐(methanylylidene))bis‐ (hydrazine‐2, 1‐diylidene))bis(methanylylidene))bis(naphthalen‐2‐ol), H2 L shows high fluorescence emission (λem, 550 nm; λabs, 420 nm) which is selectively quenched by Cu 2+ in presence of many other biologically important ions. The limit of detection (LOD), 7.3 nM is much lower than WHO recommended maximum permissible limit (20 μM) of Cu 2+ consumption in human body. The binding fashion of the probe to Cu 2+ ion is 1 : 2 mole ratio and has been confirmed by Job's plot and ESI‐MS spectral data. The binding constant for Cu 2+ is 4.93×10 10 M −2 which also indicates sufficient stability and 1 : 2 complexation. On addition of cysteine to L‐Cu 2+ ensemble, the emission intensity (550 nm) enhances which accounts the release of Cu 2+ from the non‐emissive complex and restores the total fluorogenic efficiency of probe, H2 L (LOD (Cysteine), 36 nM). Thus, ON‐OFF‐ON mechanism of H2 L has been utilized for selective and specific detection of Cu 2+ and Cysteine over several other amino acids. In addition to this, the probe is treated on WI‐38 cell line to check cytotoxicity. This chemosensor, H2 L has been successfully applied to examine intracellular trace quantity of Cu 2+ and Cysteine concentration in Hep G2 Cell lines. Abstract : The probe H2 L 1, 1′‐((1E, 1′E)‐((2E, 2′E)(((phenylazanediyl)bis(4, 1‐phenylene))bis‐(methanylylidene))bis‐(hydrazine‐2, 1‐diylidene))bis(methanylylidene))bis(naphthalen‐2‐ol) shows intense fluorescence in solution which is quenched upon addition of Cu 2+ only (in presence of 17 metal ions) while the intensity of fluorescence is restored by adding Cysteine only out of many biothiols and amino acids in 7 : 3 (v/v) CH3 CN/H2 O medium (HEPES buffer, pH 7.2. LOD data are 7.3 nM (Cu 2+ )and 36 nM (Cysteine). MTT study of probe and intracellular imaging of Cu 2+ and Cysteine in Hep G2 cells has been conducted as well.